Evergreen a guide to writing with readings - Fawcett, Susan (Wadsworth, Cengage Learning, 2014)
With carefully crafted instruction, engaging student models, and plentiful practice exercises, this best-selling text continues to provide the most effective paragraph-essay level writing instruction available.